THE VIEWS OF MUSLIM PHILOSOPHERS ON THE THEORY OF EVOLUTION - Sulaymonova Shahnoza Nodirovna (American Journals Publishing, 2024)
The article was devoted to the discussion of the views of Ibn Miskawayh and Abu Rayhan Beruni on gradual development. Philosophers' opinions on the issue reflected in the article are comparatively analyzed.